2022
DOI: 10.3389/ijph.2022.1604222
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of COVID-19 Vaccination in Italy: The Role of Trust and Experts’ Communication

Abstract: Objectives: Vaccination campaigns against COVID-19 throughout the world are not only a major organisational challenge, but also a communication and social challenge. Recent data from several countries show that a relevant proportion of citizens either do not plan to be vaccinated against COVID-19 or would rather postpone their vaccination. We argue that such attitudes are not the result of generalised scepticism about vaccination, nor of generalised distrust in science.Methods: We analysed data from three surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
2
10
0
2
Order By: Relevance
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…From a theoretical point of view, our results seem to confirm that the expected effect of subjective norms, and risk perceptions through fear of COVID-19, is mediated by trust in science. Following literature indications [ 14 , 77 , 79 , 94 , 95 , 96 , 97 ], our results also show the role of trust in science as a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Indeed, trust in science consistently emerged as a key determinant of adherence to government indications to avoid the spread of SARS-CoV-2 around the world, as several cross-national studies revealed: this has been found to be the case even regarding the most controversial issue, that is, whether to get vaccinated.…”
Section: Discussionsupporting
confidence: 87%
“…The trust in science factor has been transversally recognized as one of the factors capable of explaining different behaviors and attitudes of adherence to health behaviors prescribed in a pandemic situation [77,93]. Following literature indications [14,77,79,[94][95][96][97], trust in science seems to be a key factor, able to modulate both the emotional and social factors responsible for the intention to get vaccinated. Because of this, we formulate the following hypotheses: Hp 5: Trust mediates the relationship between subjective norms and intention to get vaccinated.…”
Section: C Modelmentioning
confidence: 99%
“…In her landmark study of visible scientists of the 1960s and 70s, A. R. S. Goodell [1975] noted that, when unusual circumstances coincide with unusual characters, the stage is set for some scientists to become highly visible in the public domain. This coincidence occurred on a global scale in 2020 -a time dominated by the Covid-19 pandemic when scientists emerged as trusted and sought-after actors [Bucchi, Fattorini & Saracino, 2022;Abdool Karim, 2022]. As politicians, civil servants, journalists, and citizens turned to scientists for guidance and reassurance, scientists became symbols of hope, media stars, and even cult figures [Kupferschmidt, 2020;Stevis-Gridneff, 2020;Fahy & Lewenstein, 2021;Naidu, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the above, for the Italian case other recent research such as Bucchi et al [ 60 ] points to positive evaluations of experts’ communication and trust in their contribution—as well as that of health institutions, local authorities and health workers—as playing a key role in understanding willingness to vaccinate. Therefore, they add that relevant implications can be drawn in terms of communication efforts and institutional strategies that are essential for building effective and inclusive vaccination campaigns.…”
Section: Introductionmentioning
confidence: 99%